Marketing Communication Strategy in Maintaining Positioning Among Consumers By PT. Federal International Finance Group Kapten Muslim Branch, Medan City - Artika Esteria Sirait; Sakhyan Asmara; Syafruddin Pohan (Britain International for Academic Research (BIAR) Publisher, 2023)
This study aims to analyze marketing communication strategies and analysis in maintaining FIF's positioning among consumers. This study used descriptive qualitative method. Data collection techniques through interviews and documentation. The analysis technique used is data reduction, data presentation, and drawing conclusions. The informants in this study consisted of three main informants and three triangulation informants. The results showed that the marketing communication strategy implemented by FIF was by identifying audiences through surveys, questionnaires and interviews regarding market wants and needs, then designing messages by holding internal meetings, then determining the methods and media used such as social media, namely Instagram, TikTok, Facebook, YouTube, print media such as brochures, billboards, banners, and electronic media such as virtual exhibitions. FIF also carried out a strategy with complete products, cheaper installments and interest, locations with offices located throughout Indonesia and at cooperating shops and dealers, and finally carried out various promotions from various online, print and electronic media. Factors that maintain FIF's positioning among the public are the ease of requirements, the speed of the application process until disbursement, the friendliness of the employees, the many attractive offers such as promos delivered directly via WhatsApp, SMS, or telephone calls to consumers, finally the prizes given.